Antivaccine Messages on Facebook: Preliminary Audit - Dhaliwal, Dhamanpreet; Mannion, Cynthia (JMIR Publications, 2020)
BackgroundThe World Health Organization lists vaccine hesitancy as one of 10 threats to global health. The antivaccine movement uses Facebook to promote messages on the alleged dangers and consequences of vaccinating, leading to a reluctance to immunize against preventable communicable diseases. ObjectiveWe would like to know more about the messages these websites are sharing via social media that can influence readers and consumers. What messages is the public receiving on Facebook about immunization? What content (news articles, testimonials, videos, scientific studies) is being promoted? MethodsWe proposed using a social media audit tool and 3 categorical lists to capture information on websites and posts, respectively. The keywords "vaccine," "vaccine truth," and "anti-vax" were entered in the Facebook search bar. A Facebook page was examined if it had between 2500 and 150,000 likes. Data about beliefs, calls to action, and testimonials were recorded from posts and listed under the categories Myths, Truths, and Consequences. Website data were entered in a social media audit template. ResultsUsers' posts reflected fear and vaccine hesitancy resulting from the alleged dangers of immunization featured on the website links. Vaccines were blamed for afflictions such as autism, cancer, and infertility. Mothers shared testimonies on alleged consequences their children suffered due to immunization, which have influenced other parents to not vaccinate their children. Users denied the current measles outbreaks in the United States to be true, retaliating against the government in protests for fabricating news. ConclusionsSome Facebook messages encourage prevailing myths about the safety and consequences of vaccines and likely contribute to parents' vaccine hesitancy. Deeply concerning is the mistrust social media has the potential to cast upon the relationship between health care providers and the public. A grasp of common misconceptions can help support health care provider practice.